THE PAID-IN CAPITAL AS THE INDICATOR OF GOODWILL ASSESSMENT - Evgeni I. Ponomarev; Gegetsik A. Tovmasyan; Lily S. Malaveryan (Статистика и экономика)
The article considers the problem of the goodwill assessment of joint-stock companies through the indicator of the paid-in capital. It allows to estimate and to forecast objectively the results and risks of investment activity.